2007
DOI: 10.1021/ac061878x
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Nanopore Array Electrodes by Focused Ion Beam Milling

Abstract: Single nanopore electrodes and nanopore electrode arrays have been fabricated using a focused ion beam (FIB) method. High aspect ratio pores (approximately 150-400-nm diameter and 500-nm depth) were fabricated using direct-write local ion milling of a silicon nitride layer over a buried platinum electrode. This local milling results in formation of a recessed platinum electrode at the base of each nanopore. The electrochemical properties of these nanopore metal electrodes have been characterized by voltammetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
174
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 192 publications
(185 citation statements)
references
References 39 publications
8
174
2
1
Order By: Relevance
“…Despite this diffusional overlap, at low scan rates (<100 mV s --1 ) sigmoidal voltammograms were observed for all arrays with all achieving steady-state currents see Fig 5(a). This is in agreement with previous reports using nanoscale electrode arrays [8,16,30] and arises from partial and complete diffusional overlap, where the nanowire array it behaves as ultra-microelectrode of the same size of the total array, i.e., the width of a six nanowire array is 6.6 m. Such ultramicroelectrodes also experience enhanced mass transport and exhibit sigmoidal behaviour and steady-state currents.…”
Section: Analysis Of Electrochemical Behaviour At Nanowire Arrayssupporting
confidence: 93%
See 4 more Smart Citations
“…Despite this diffusional overlap, at low scan rates (<100 mV s --1 ) sigmoidal voltammograms were observed for all arrays with all achieving steady-state currents see Fig 5(a). This is in agreement with previous reports using nanoscale electrode arrays [8,16,30] and arises from partial and complete diffusional overlap, where the nanowire array it behaves as ultra-microelectrode of the same size of the total array, i.e., the width of a six nanowire array is 6.6 m. Such ultramicroelectrodes also experience enhanced mass transport and exhibit sigmoidal behaviour and steady-state currents.…”
Section: Analysis Of Electrochemical Behaviour At Nanowire Arrayssupporting
confidence: 93%
“…In these works, it was found that the underlying metallisation dominated to the overall capacitance, such that the creation of extra nanopore electrodes did not affect the measured capacitance. [8,20,35] We also found this to be true for the nanowire electrode arrays, whereby increasing the number of nanowires present in the array did not affect the measured capacitive response.…”
Section: Characterisation Of Capacitive Contributionsmentioning
confidence: 53%
See 3 more Smart Citations